2020
DOI: 10.1111/iej.13369
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory study of the impact of ultraconservative access cavities and minimal root canal tapers on the ability to shape canals in extracted mandibular molars and their fracture resistance

Abstract: mandibular molars. No differences were observed in shaping ability and fracture resistance between .03 and .05 taper canal preparations. Apical preparation with larger instruments resulted in significantly less untouched canal area in all groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 52 publications
3
62
0
1
Order By: Relevance
“…Transportation is defined as deviations of the prepared root canal in comparison with its original natural axis, whilst centring ability reflects the ability for instruments to remain centred within the root canal (Gambill et al 1996). In this study, there were no differences amongst the three access groups tested (TEC, CEC and TAC) with regard to centring ability and canal transportation, which is corroborated by the findings of Moore et al (2016) and Augusto et al (2020). Nonetheless, previous studies (Rover et al 2017, Alovisi et al 2018 have reported greater apical transportation in CEC groups in comparison with TEC groups, which is likely due to the instruments chosen for the preparations.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Transportation is defined as deviations of the prepared root canal in comparison with its original natural axis, whilst centring ability reflects the ability for instruments to remain centred within the root canal (Gambill et al 1996). In this study, there were no differences amongst the three access groups tested (TEC, CEC and TAC) with regard to centring ability and canal transportation, which is corroborated by the findings of Moore et al (2016) and Augusto et al (2020). Nonetheless, previous studies (Rover et al 2017, Alovisi et al 2018 have reported greater apical transportation in CEC groups in comparison with TEC groups, which is likely due to the instruments chosen for the preparations.…”
Section: Discussionsupporting
confidence: 76%
“…That is likely due to the restoration process to which specimens were subjected before the tests, as it has been shown that restored teeth can regain up to 72% of their original resistance to fracture, when compared to untreated teeth (Hamouda &Shehata 2011, Moore et al 2016. These findings are in line with most studies in the literature that tested TEC and CEC groups (Moore et al 2016, Chlup et al 2017, Rover et al 2017, Ivanoff et al 2017, Sabeti et al 2018, Augusto et al 2020, as well as that of Corsentino et al (2018), which was performed on mandibular molars and tested TEC, CEC and TAC groups. Amongst minimally invasive access studies, four reported differences regarding resistance to fracture amongst teeth subjected to different endodontic access cavity designs (Krishan et al 2014, Plotino et al 2017, Zhang et al 2019, Abou-Elnaga et al 2019.…”
Section: Discussionsupporting
confidence: 65%
“…These results were expected as minimal access cavities aim to decrease the amount of tooth tissue removal based on the assumption that the preservation of these structures might increase the fracture resistance of root filled teeth. However, several studies concluded that the size of the access cavity does not increase the fracture resistance of root filled teeth (Rover et al 2017,Özyürek et al 2018, Silva et al 2018, Augusto et al 2020. In theory, traditional access cavities that have larger restorations (Table 1) than minimal cavities should be related to a greater number of restorative deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…Its main objective is to apply those principles to root canal treatment, thus maintaining as much tooth structure as possible. The issue of MIE access cavities has undoubtedly dominated recent discussions in the literature (Moore et al 2016, Rover et al 2017, Neelakantan et al 2018, Silva et al 2018a,b, 2020, Augusto et al 2020, Mendes et al 2020. However, the concept behind MIE is broader than the sole question of endodontic access cavities.…”
Section: Introductionmentioning
confidence: 99%